2009
DOI: 10.1016/j.jaut.2009.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Primary biliary cirrhosis is associated with altered hepatic microRNA expression

Abstract: MicroRNAs (miRNAs) are small RNA molecules that negatively regulate protein coding gene expression and are thought to play a critical role in many biological processes. Aberrant levels of miRNAs have been associated with numerous diseases and cancers, and as such, miRNAs have gain much interests as diagnostic biomarkers, and as therapeutic targets. However, their role in autoimmunity is largely unknown. The aims of this study are to: (1) identify differentially expressed miRNAs in human primary biliary cirrhos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
126
2
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 193 publications
(135 citation statements)
references
References 51 publications
6
126
2
1
Order By: Relevance
“…Padgett et al observed that a total of 35 independent miRNAs in the miRNA expression profile are disordered and that miR-26a is one of the down-regulated miRNAs. The predicted targets of these alternative miRNAs are known to affect cell proliferation, apoptosis, inflammation, oxidative stress and metabolism associated with the development of PBC (31). The roles that miR-26 plays in non-tumor diseases have yet to be clarified, and further studies are required.…”
Section: Mir-26 and Non-tumor Diseasementioning
confidence: 99%
“…Padgett et al observed that a total of 35 independent miRNAs in the miRNA expression profile are disordered and that miR-26a is one of the down-regulated miRNAs. The predicted targets of these alternative miRNAs are known to affect cell proliferation, apoptosis, inflammation, oxidative stress and metabolism associated with the development of PBC (31). The roles that miR-26 plays in non-tumor diseases have yet to be clarified, and further studies are required.…”
Section: Mir-26 and Non-tumor Diseasementioning
confidence: 99%
“…24). miR-122 is an abundant, liver-specific miRNA (25,26) whose expression is decreased in advanced liver diseases, such as cirrhosis (27) and hepatocellular carcinoma (28,29). Several independent studies demonstrate that in vivo inhibition of miR-122 reduces systemic cholesterol levels by as-yet unidentified molecular mechanisms (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…The finding that miR-122 regulates systemic iron homeostasis adds to a growing list of liver functions that are controlled by miR-122. For example, miR-122 levels are decreased in advanced liver diseases such as cirrhosis and hepatocellular carcinoma pathologies known to be exacerbated by increased liver iron levels [95][96][97][98].…”
Section: Mir-122-mediated Regulation Of Systemic Ironmentioning
confidence: 99%